Gestión administrativa financiera en la operatividad del benemérito cuerpo de bomberos MYR. Francisco Zamora del cantón El Empalme y su incidencia en el desarrollo administrativo período 2010-2012 - Arcentales Torres, Nelly Elizabeth (2014)
The management is to provide administrative support to the business processes of the different functional areas of an entity, in order to achieve effective results and with a great competitive advantage disclosed in financial statements. In this research it was determined that the revenue grew by 2.78 % per annum on average, while the income coded increased at the 3.48 % in the period 2010 - 2012. On the expenditure side, the budget has the same growth rate of the income, while the encoding of the expenditure amounted to 2.81 % in the same period of time. The research also helped to identify that the 47.37 % of the operating staff, if you know that the management involves the organization as a whole. In the administrative area understanding reaches 83.33 % dominated, while by the side of the managers the knowledge on this theme reaches 80 %. The financial information generated through the various financial statements and budget cards are for the 57.89 % of the operating staff very reliable, for the administrative staff is 100% and the 80% of the management is very reliable. According to the 84.21 % of the operating staff, timely decisions on the part of the management and administration has strengthened the institutional management and its operational capacity, the 63.16 % of those estimated to have carried out a proper management. Good management, administrative and operational fire corps is reflected in the healthy indicators of effectiveness, efficiency and effectiveness achieved; in almost all the years reach 100% with the exception of the earnings for the year 2012, where the effectiveness is 80 %.